Effect of unilateral misfit on preload of retention screws of implant-supported prostheses submitted to mechanical cycling - Assunção, Wirley Goncalves [UNESP]; Barão, Valentim Adelino Ricardo [UNESP]; Delben, Juliana Aparecida [UNESP]; Gomes, Érica Alves [UNESP]; Garcia, Idelmo Rangel [UNESP] (Japan Prosthodontic Society, 2011)
Purpose: The aim of this study was to evaluate the effect of different levels of unilateral angular misfit on preload maintenance of retention screws of single implant-supported prostheses submitted to mechanical cycling. Materials and methods: Premachined UCLA abutments were cast with cobalt-chromium alloy to obtain 48 crowns divided into four groups (n=12). The crowns presented no misfit in Group A (control group) and unilateral misfits of 50μm, 100μm and 200μm in the groups B, C and D, respectively. The crowns were attached to external hexagon implants with a titanium retention screw with torque of 30N/cm. Oblique loading of 130N at 2Hz was applied on each replica, totalizing 5×104 and 1×106cycles. Detorque values were measured initially and after each cycling period. Data were evaluated by analysis of variance and Tukey's HSD test (p<0.05). Results: All groups presented reduced initial detorque values (p< 0.05) in comparison to the insertion torque (30. ± 0.5. N/cm) and Group A (25.18. N/cm) exhibited the lowest reduction. After mechanical cycling, all groups presented detorque values from 19.5. N/cm to 22.38. N/cm and the mechanical cycling did not statistically influence the detorque values regardless the misfit level of the replicas. Conclusion: The unilateral misfit influenced the preload maintenance only before mechanical cycling. The mechanical cycling did not influence the torque reduction. © 2010 Japan Prosthodontic Society.
Keywords: Dental implant; Implant-supported prosthesis; Mechanical cycling; Misfit; Preload; chromium derivative; dental alloy; dental care; denture; mechanical stress; methodology; prosthesis; tooth crown; tooth prosthesis; torque; Chromium Alloys; Crowns; Dental Abutments; Dental Alloys; Dental Prosthesis Design; Dental Prosthesis Retention; Dental Prosthesis, Implant-Supported; Dental Stress Analysis; Prosthesis Fitting; Stress, Mechanical; Torque